Cold Atmospheric Plasma Conveys Selectivity Against Hepatocellular Carcinoma Cells via Triggering EGFR(Tyr1068)-Mediated Autophagy - Wang, Danjun; Zhang, Jianying; Cai, Linhan; Dai, Xiaofeng (Frontiers in Oncology, 2022)
Hepatocellular carcinomas remain as a global health threat given its high mortality rate. We have previously identified the selectivity of cold atmospheric plasma (CAP) against multiple types of malignant tumors and proposed it as a promising onco-therapeutic strategy. Here, we investigated its roles in controlling hepatocellular carcinoma malignancy and one possible driving molecular mechanism. By focusing on post-translational modifications including acetylation, phosphorylation, and ubiquitination, we identified the crosstalk between EGFR acetylation and EGFR(Tyr1068) phosphorylation and their collective roles in determining LC3B ubiquitination and proposed the EGFR/p-JNK/BIRC6/LC3B axis in CAP-triggered autophagy. Our study not only demonstrated the selectivity of CAP against hepatocellular carcinoma malignancy and confirmed its roles as an onco-therapeutic tool but also opened the horizon of translating CAP into clinics toward a broader scope that included human longevity and anti-aging.